2021
DOI: 10.1253/circj.cj-20-0823
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Frailty Score Predicts Long-Term Mortality and Hospitalization Due to Heart Failure After Implantation of Cardiac Implantable Electric Device

Abstract: physical activity time, which was determined by pacemakers after implantation, was associated with mortality. 7 To our knowledge, however, no study has investigated both life expectancy and the frequency of hospitalization due to HF after several types of CIED in these patients, and data in support of decision making are unavailable.Here, as part of efforts to establish indications for CIED treatment in aged patients with low ADL status, we investigated the association between CFS and prognosis in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Of the included studies, 13 studies were considered of having a high risk of bias [ 7 , 31 , 32 , 39 , 41 , 43 , 46 , 52 , 53 , 60 , 61 , 63 , 64 ], 16 as moderate risk of bias [ 18 , 29 , 33 , 36 , 37 , 42 , 44 , 45 , 48 50 , 55 , 56 , 58 , 59 , 62 ], and 12 studies had a low risk [ 28 , 30 , 34 , 35 , 38 , 40 , 47 , 51 , 54 , 57 , 65 , 66 ] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 13 studies were considered of having a high risk of bias [ 7 , 31 , 32 , 39 , 41 , 43 , 46 , 52 , 53 , 60 , 61 , 63 , 64 ], 16 as moderate risk of bias [ 18 , 29 , 33 , 36 , 37 , 42 , 44 , 45 , 48 50 , 55 , 56 , 58 , 59 , 62 ], and 12 studies had a low risk [ 28 , 30 , 34 , 35 , 38 , 40 , 47 , 51 , 54 , 57 , 65 , 66 ] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies indicated similar results in which the severity of pre-operative frailty was associated with poor clinical outcomes in patients with other cardiovascular diseases. These include critical limb ischemia patients who underwent bypass surgery [ 33 ]; heart failure patients who experienced implantation of cardiac implantable electric devices [ 34 ]; atrial fibrillation patients who undertook catheter ablation [ 35 ]; and CAD patients who underwent CABG [ 36 ]. However, there is limited data on the clinical outcomes of older frail patients with stable CAD who underwent elective PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of clear etiologies in primary care, clinicians should also consider identifying the potential malignant phenotype that might affect patient prognosis. Based on the previously mentioned AVB severity and LV change, AVB patients with unknown etiologies were divided into four types with distinctive characteristics, of which 17% showed risk features such as advanced AVB, increased LVEDD, and high NT-proBNP levels [ 35 , 36 ] and were classified as the severe phenotype. Among AVB patients with undetermined etiologies who received pacemakers, those who presented with severe phenotype were associated with a triple risk of developing HF symptoms and signs.…”
Section: Discussionmentioning
confidence: 99%